(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Cleft Lip and Palate (CLP) are one of the most frequently occurring craniofacial congenital anomalies. Itimpairs an individual’s aesthetics, speech, hearing, and psychological and social life. Respiratory difficulty and feeding problems are the primary concern of cleft palate newborns. Case Presentation: A 17-day-old newborn presented to the Neonatal Intensive Care Unit on 10 January 2023 with difficulty in respiration and causes nasal regurgitation. Then the patient was referred to dental OPD to place a palatal device/obturator. The case presented here discusses the management of breathing problems to halt cyanosis in a neonate with a cleft palate. Conclusion: Another immediate problem for a newborn with a cleft lip/palate is difficulty in feeding. After adjusting an obturator to the patient’s mouth, she recovered from cyanosis. Currently, she is pretty comfortable in respiration as well as feeding. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 104-107